Effect of acute gamma irradiation on flower, bulb characters and stability of mutants in tuberose (Polianthes tuberosa) - JYOTHI, R; SINGH, K P (The Indian Journal of Agricultural Sciences, 2017)
Genetic variability is the prerequisite for any crop to be improved. Mutation breeding is a best method identified to enhance the genetic variability in crops within short time. Knowing the limited variability in tuberose (Polianthes tuberosa), present investigation was undertaken for the improvement in this crop by utilizing the cultivars Phule Rajani and Prajwal. To induce variation, gamma radiation (2.5 - 15 Gy) was applied and the effect on flower and bulb characters were assessed in M1 generation. With increase in doses of gamma irradiation, gradual reduction in number of spikes, flower number, number of bulb, weight of bulb and bulb diameter was observed. In some cases lower dose was found simulative, while higher dose had inhibitory effect on morphological variation. Various macro mutations were scored for uniform flowering, reduced number of bulbs and spike number in M1 population. The mutants of VM1 generation not found stable in VM2 generation. But we could able to find the some more mutants from the maintained gamma irradiated population of VM2 generation related to change in flower shape. In general, freshly harvest tuberose bulbs of cv. Prajwal and Phuel Rajani responded more to gamma irradiation. From this study, it has found that gamma irradiation level, 7.5 Gy and 10.0 Gy were found optimal for mutation induction in these two tuberose cultivars.